Tipologia e traduzione dei verbi di moto italiani — analisi semantica - Marcol-Cacoń, Lucyna (Neophilologica, 2016)
The aim of the present paper is to present and discuss the differences between Italian and Polish verbs of motion in terms of lexis and semantics. The classification of verbs of motion on the basis of the above listed criteria is aimed at bearing out the hypothesis that many Italian verbs communicate modality of the action of motion as well as a direction of motion. Furthermore, several possible translator’s dilemmas are outlined and an emphasis is put on the processes which are crucial in order to select the best possible Polish equivalent of the verbs under consideration here.